Changemakers! : practitioners advance equity and access in out-of-school time programs - Hill, Sara; Vance, Femi (Current issues in out-of-school time., 2019)
"A foundational tenet of the Out-of-School Time (OST) field is that all youth deserve impactful and engaging learning experiences. That requires that organizations, programs, and OST professionals remain responsive to the emerging needs of their diverse youth population and the communities in which they live. This book illustrates the tensions that arise when organizations and OST professionals try to engage all youth, especially the underserved - when infrastructure, funding, and mindsets have not kept pace with the evolving needs of youth and their communities. The issues raised in this book - funding, outreach, engagement of immigrant families - have yet to be fully explored with an equity lens. Within these broad topics, this book will bring to the surface the equity and access challenges as well as posit solutions and strategies. Each chapter is written from an insider's perspective, by practitioners themselves, who articulate some of the key, and relevant issues in the field. Each chapter ends with a Research-Practice Connection section written by the editors, which discusses the topic from a research lens, and generates a set of questions that can be used by researchers in future studies to explore the topic in a more in-depth, and expansive manner"--